2011
DOI: 10.1124/jpet.111.186874
|View full text |Cite
|
Sign up to set email alerts
|

Pleiotropic Opioid Regulation of Spinal Endomorphin 2 Release and Its Adaptations to Opioid Withdrawal Are Sexually Dimorphic

Abstract: We studied adaptations to acute precipitated opioid withdrawal of spinal -opioid receptor (MOR)-coupled regulation of the release of endomorphin 2 (EM2). The release of this highly MOR-selective endogenous opioid from opioid-naive spinal tissue of male rats is subjected to MOR-coupled positive as well as negative modulation via cholera toxin-sensitive G s and pertussis toxin-sensitive G i /G o , respectively. The net effect of this concomitant bidirectional modulation is inhibitory. MOR-coupled pleiotropic reg… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

2
25
0
1

Year Published

2012
2012
2021
2021

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 16 publications
(28 citation statements)
references
References 30 publications
2
25
0
1
Order By: Relevance
“…This was attributed to increased βAR-Gs coupling because there was no difference in βAR affinity or number and responses to forskolin or GTP-γ-S were comparable between male and female hepatocytes [54]. Sex differences in μ-opioid receptor (MOR) coupling to G-proteins have been suggested to play a role in differential adaptation to opiate withdrawal in the spinal cord [55]. Here the release of the potent endogeous opioid, endomorphin 2, is regulated by MOR, which inhibits release through a Gi-protein coupled mechanism.…”
Section: Sex Biased Signaling Of Other Receptorsmentioning
confidence: 99%
“…This was attributed to increased βAR-Gs coupling because there was no difference in βAR affinity or number and responses to forskolin or GTP-γ-S were comparable between male and female hepatocytes [54]. Sex differences in μ-opioid receptor (MOR) coupling to G-proteins have been suggested to play a role in differential adaptation to opiate withdrawal in the spinal cord [55]. Here the release of the potent endogeous opioid, endomorphin 2, is regulated by MOR, which inhibits release through a Gi-protein coupled mechanism.…”
Section: Sex Biased Signaling Of Other Receptorsmentioning
confidence: 99%
“…The release of the endogenous opioid, endomorphin 2 (EM2), is regulated by both positive and negative feedback systems that are activated following the binding of EM2 to μOR autoreceptors in the spinal cord. In males, the activated μOR can couple with either Gs or Gi/o, which respectively enhance and inhibit subsequent EM2 release [387]. Under normal conditions, the negative feedback pathway predominates; however, following morphine withdrawal, compensatory mechanisms kick in that shift the balance towards favoring Gs coupling and enhanced EM2 release.…”
Section: Introductionmentioning
confidence: 99%
“…sufentanil augmented spinal EM2 release contrasts with our previous finding that MOR-mediated modulation of neurotransmitter release and intracellular signaling in vitro is bimodal, with stimulatory (G s -mediated) and inhibitory (G i -mediated) effects occurring at low and high concentrations of MOR agonist, respectively. 10,34,36,95,99 Multiple factors could account for the current ability of a seemingly high dose of i.t. sufentanil to facilitate EM2 release: (1) An i.t.…”
Section: Discussionmentioning
confidence: 99%
“…We previously reported that sufentanil enhances in vitro K + -induced release of EM2, an effect that was observable only following in vitro pretreatment with pertussis toxin 10 to eliminate MOR-mediated inhibition of K + -induced EM2 release. 10,36 However, the contribution of endogenous EM2 to spinal antinociception resulting from intrathecally administered MOR agonists, and the mechanisms thereof, were not studied. Such knowledge could hold a key to harnessing endogenous opioids for pain management.…”
Section: Introductionmentioning
confidence: 98%